Histopathologic and Autopsy Findings in Patients Diagnosed With Coronavirus Disease 2019 (COVID-19): What We Know So Far Based on Correlation With Clinical, Morphologic and Pathobiological Aspects. (November 2020) - Al Nemer, Areej
Abstract : In response to the current outbreak of Coronavirus Disease-2019 (COVID-19), a fast body of literature emerged providing insights into the clinical and radiologic aspects of the novel disease, while the pathologic manifestations on tissue are yet to be sufficiently characterized mainly due to paucity of autopsy and biopsy of these cases. It is essential for both the clinicians and pathologists to maintain up-to-date knowledge of this continuously evolving topic in the midst of the current pandemic. Besides, understanding the impact of any disease in tissue pathology is crucial for better analysis of the pathogenesis and speculation of potential therapeutic targets. This review aimed to highlight the potential implication of COVID-19 in the pathology of various organ systems. We discuss the pathologic findings of the lungs, gastrointestinal tract, liver, brain, kidneys, heart, and the reproductive and immune systems that are associated with COVID-19. It seems that the respiratory, immune, and the digestive systems are the major targets of the disease. Mild mononuclear inflammatory cell infiltration is the most frequent histologic finding in general. Besides organ-specific changes, microthrombi, especially noticed in lungs, kidneys, and prostates, are the most significant observation microscopically. In addition, the possible mechanisms of organ injury were also reviewed.